Chemical control of the coffee berry borer with Cyantranilipole - de Souza, Júlio César; Reis, Paulo Rebelles; Silva, Rogério Antonio; Carvalho, Thiago Alves Ferreira de; Pereira, Andreane Bastos (Coffee Science - ISSN 1984-3909, 2014)
Hypothenemus hampei (Ferrari, 1867) (Coleoptera: Curculionidae, Scolytinae) is a worldwide coffee pest. It is the most important pest to Coffea canephora Pierre & Froehner and the second to Coffea arabica L. in Brazil. The chemical control is the most efficient method to its control and the endosulfan is the most efficient chemical. This ciclodieno chlorinated compound is permitted in Brazil until July 2013. The objective of this study was to observe the efficiency of the cyantraniliprole 100 OD insecticide in spraying system to coffee berry borer control compared to the endosulfan 350 EC. The cyantraniliprole was sprayed at doses of 0.75, 1.0, 1.25, 1.5, 1.75, 2.0 liters c.p. /ha and endosulfan at 1.5 and 2.0 liters c.p. /ha. Two applications with 30 days interval were used at the “transit” time of the berry borer. Efficiency of the products was evaluated by counting the number of the living borer inside of damaged fruits in a liter of coffee (around 700 fruits) collected randomly in plots. All treatments differed from the control treatment but did not differ among them. Control treatment showed 35.7% of living borer, while doses of 1.75 and 2.0 liters of cyantraniliprole/ha, 3.5 and 4.0%, respectively. Treatment with endosulfan at 1.5 and 2.0 liters/ha showed 1.0 and 0.8% of living borer, respectively, and did not differ from cyantraniliprole. The results indicate that the cyantraniliprole 100 OD is effective in controlling H. hampei at doses between 1.75 and 2.0 liters /ha with two spraying.